The implications of thuggery as a form of political violence in Bauch, Nigeria - Ilelah, Kabiru Bello; Ab Halim, Adlina; Ku Shamsu, Ku Hasnita (Elixir, 2015)
Security challenges have remained a worried concern, as the activities of political thuggery in a form of violence becoming rampant in most societies of Nigeria. The utilization of thuggery in the process of attaining and preservation of political power has become a fashion to most of the politicians. This study tends to examine the implications of political thuggery in Bauchi, Nigeria. Hence, the qualitative method was used to collect data. The study reveals, through the use of thuggery, insurgency, small arms proliferation, violence and incompetent leaders emerge in the society. Eradication of poverty and education programs should be given due attention by the government.